Situ Gunung Nature Tourism Park: Applying the Ecotourism Principle of The International Ecotourism Society (TIES) - Ansharil Haq, Ramiz; Manalu, Triana; Habibi, Ahmad (International Journal of Green Tourism Research and Applications, 2025)
This study analyses the application of eight ecotourism principles set forth by The International Ecotourism Society (TIES) in Situ Gunung Ecotourism, Sukabumi, West Java, Indonesia. The study adopts a qualitative methodology incorporating Focus Group Discussions with destination managers, tour guides, and security staff. The research assesses the conformity of Situ Gunung’s Ecotourism activities with the concepts of TIES. Research demonstrates that Situ Gunung successfully alleviates environmental repercussions by measures including visitation restrictions, bans on animal feeding, and sustainable infrastructure development. Environmental and cultural education is advanced through community involvement, signage, and traditional performances such as Degungan and Kecapi Suling music at the Amphitheater. The suspension bridge and additional attractions are sustainably maintained through regular safety assessments. Community empowerment is manifested through local engagement in tourism activities, cultural conservation, and infrastructure administration. The study concludes that Situ Gunung effectively incorporates TIES concepts, harmonizing tourism development with environmental and cultural sustainability. The report advocates for the enhancement of cultural preservation programs and the implementation of transparent revenue management to bolster the long-term sustainability of ecotourism. Situ Gunung exemplifies sustainable ecotourism, illustrating the utilization of natural and cultural resources for community empowerment and environmental preservation.